A low-carbon cementitious material for preparing high-speed roadbed and preparation method thereof
By modifying the main components of the gelling material and introducing modified gypsum and carbon citrate quantum doping red mud, the problems of inadequate settling time and insufficient strength of the gelling material are solved, and a suitable final settling time and high-strength gelling material are achieved.
Patent Information
- Application Number
- CN202510000303.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The final settling time of existing gelling materials is not suitable, and the compressive strength and flexural strength are low, which affects their actual use.
By aminating the ore powder, thiolating the fly ash, and introducing modified gypsum and carbon citrate quantum doping red mud, low-carbon gelled materials with high-speed roadbed were prepared.
It effectively shortens the final set time of gelled materials and significantly improves its compressive strength and flexural strength, making it suitable for engineering applications of high-speed roadbeds.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a low-carbon cementitious material for preparing a highway roadbed and a preparation method thereof. Background Art
[0002] With the rapid development of infrastructure construction in my country, the annual use of road pavement base materials exceeds 3 billion tons; natural soil and stone materials and cementitious materials are trying to use industrial solid waste to partially or completely replace the raw materials of road pavement base, which has also become an effective way to deal with large-scale solid waste. Red mud contains free alkalis such as sodium hydroxide and sodium carbonate and bound alkalis such as sodalite and cancrystal. By using the strong alkalinity of red mud to stimulate active substances such as Si and Al in cementitious materials, silicates and aluminates can be depolymerized and repolymerized.
[0003] The patent application with publication number CN117024014A discloses a low-carbon anti-seepage early-strength water-reducing cementitious material and its preparation method. After the cementitious material of the patent application is mixed with water, the cement clinker in the active component undergoes a hydration reaction, and the slag powder, fly ash, calcined coal gangue powder and calcined red mud powder undergo a volcanic ash reaction to produce a reaction product that can provide certain strength performance. The filling component can play a supporting role similar to that of aggregates, and as a connecting node, it forms a network structure together with the reaction product produced by the active component when it encounters water. However, the patent does not solve the problem that the final setting time of the existing cementitious materials is not suitable, and the compressive strength and flexural strength are low, which seriously affects its actual use.
[0004] Therefore, how to prepare low-carbon cementitious materials for highway roadbeds by modifying the main components of cementitious materials such as mineral powder, fly ash, gypsum and red mud, ensure that the cementitious materials have a suitable final setting time, and effectively improve the compressive strength and flexural strength has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a low-carbon cementitious material for preparing a highway roadbed and a preparation method thereof, aiming to solve the problems of the incompatibility of the final setting time of the existing cementitious materials and the low compressive strength and flexural strength.
[0006] The present invention prepares a low-carbon cementitious material for a highway roadbed by subjecting the main component of the cementitious material, the mineral powder, to an amination treatment, subjecting the fly ash to a thiol treatment, and introducing modified gypsum and citric acid carbon quantum dots to dope red mud, thereby ensuring that the cementitious material has a suitable final setting time and effectively improving the compressive strength and flexural strength.
[0007] The technical solution of the present invention is as follows:
[0008] The first aspect of the present invention provides a method for preparing a low-carbon cementitious material for preparing a highway roadbed, comprising the following steps:
[0009] Step S1: weigh 100-120 parts of mineral powder by weight, add it to 450-500 parts of anhydrous ethanol, and disperse it by ultrasonic for 1-2 hours to obtain a suspension; add 20-25 parts of DL-alanine to the suspension, heat it to 75-80°C and stir it for 0.5-1 hour, and obtain the amination mineral powder after filtering, washing and drying;
[0010] Step S2: In parts by weight, 40 to 70 parts of amination ore powder, 10 to 30 parts of fly ash and 5 to 20 parts of gypsum are added to 100 to 140 parts of deionized water for a first stirring treatment, and then 2 to 15 parts of red mud are added for a second stirring treatment to obtain a low-carbon cementitious material for preparing a highway roadbed.
[0011] Amination of mineral powder changes the charge characteristics of cementitious materials, reduces the electrostatic repulsion between particles, makes the particles easier to approach and react, and accelerates the hydration rate; at the same time, the modified mineral powder can provide additional nucleation points, which promotes the faster formation of more hydration products, thereby reducing the final setting time.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] As a preferred technical solution of the present invention, the fly ash is thiolated fly ash; the preparation method of the thiolated fly ash comprises: mixing 80 to 90 parts of anhydrous ethanol, 10 to 20 parts of deionized water and 4 to 6 parts of ammonia water by weight, stirring for 10 to 20 minutes at 30 to 40°C, then adding 16 to 20 parts of fly ash and 2 to 4 parts of (3-mercaptopropyl) triethoxysilane and stirring for 20 to 24 hours, centrifuging to obtain a solid after the reaction is completed, washing the solid with anhydrous ethanol, and drying to obtain the thiolated fly ash.
[0014] After modification, thiolated fly ash has better dispersibility and can be better filled into the gaps between cementitious material particles, increasing the density of the material, reducing the porosity, and thus improving the compressive strength; at the same time, thiolated fly ash can absorb moisture to a certain extent, maintain internal humidity, and prevent volume shrinkage and cracking caused by rapid water loss, thereby maintaining a higher compressive strength.
[0015] As a preferred technical solution of the present invention, the gypsum is modified gypsum; the preparation method of the modified gypsum comprises: in parts by weight, 30 to 45 parts of anhydrous ethanol and 10 to 15 parts of deionized water are evenly mixed, the pH is adjusted to 4.2 to 4.8 with glacial acetic acid, and then 2 to 4 parts of γ-glycidyloxypropyltrimethoxysilane and 8 to 10 parts of gypsum are added and stirred for 40 to 60 minutes, filtered, washed, and dried to obtain the modified gypsum.
[0016] The modified gypsum is surface treated with γ-glycidyloxypropyltrimethoxysilane to introduce epoxy groups. The epoxy groups can form a network structure inside the material, preventing cracks from rapidly extending from one area to the entire material, thereby improving the material's flexural resistance.
[0017] As a preferred technical solution of the present invention, the red mud is citric acid carbon quantum dots doped red mud; the preparation method of the citric acid carbon quantum dots doped red mud comprises: adding 2 to 4 parts of glacial acetic acid to 180 to 200 parts of deionized water, adding 16 to 20 parts of red mud and 6 to 8 parts of citric acid carbon quantum dots, stirring for 2 to 4 hours, freezing at -4°C for 20 to 24 hours, and then vacuum freeze-drying to obtain the citric acid carbon quantum dots doped red mud.
[0018] As a preferred technical solution of the present invention, the vacuum freeze-drying conditions include: vacuum degree of 8~12Pa, temperature of -20~-30°C, and time of 48~72h.
[0019] As a preferred technical solution of the present invention, the preparation method of the citric acid carbon quantum dots comprises: in parts by weight, 2 to 4 parts of citric acid are evenly spread on the bottom of a beaker, and heat treated in a vacuum drying oven; after the heat treatment is completed, it is naturally cooled to room temperature to obtain a solid, and then 10 to 14 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L is added to the solid, stirred evenly, and dialyzed, freeze-dried, and ground to obtain the citric acid carbon quantum dots.
[0020] As a preferred technical solution of the present invention, the temperature of the heat treatment is 200-220° C. and the time is 1-2 hours.
[0021] The small size of the citrate carbon quantum dots in the red mud enables them to fill the gaps between the red mud particles, thereby increasing the density of the material, reducing the porosity, and further improving the flexural strength of the cementitious material.
[0022] As a preferred technical solution of the present invention, the stirring speed of the first stirring treatment is 600-800 r / min, and the stirring time is 4-8 min.
[0023] As a preferred technical solution of the present invention, the stirring speed of the second stirring treatment is 300-400 r / min, and the stirring time is 10-15 min.
[0024] The second aspect of the present invention provides a low-carbon cementitious material for preparing a highway roadbed, which is prepared by the method described in the first aspect.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The modified gypsum of the present invention is surface treated with γ-glycidyloxypropyltrimethoxysilane to introduce epoxy groups. As an active group, the epoxy group can be combined with the amino group of the aminated mineral powder and can also react with the thiol group of the thiolated fly ash. During the reaction of the citric acid carbon quantum dots doped with red mud, the CH bonds in the citric acid are gradually oxidized into carboxyl groups, and some CC bonds are broken or reorganized. As the citric acid molecules are continuously carbonized, the surface carboxyl groups are continuously enriched, and the carboxyl groups with high reactivity can also react with the modified gypsum. Based on the modified gypsum, an interpenetrating network structure is constructed, which can not only shorten the final setting time, but also effectively improve the compressive strength and flexural strength of the cementitious material.
[0027] 2. The cementitious material of the present invention utilizes the synergistic reaction between multiple solid wastes. The CSH gel and ettringite and other products generated by hydration overlap with each other to form a skeleton and fill the pores. As the density increases, the strength of the solidified body continues to increase, so that the cementitious material has excellent properties such as good volume stability and high strength, and can be widely used in engineering fields such as roadbed water-stabilizing layer and large-volume concrete.
[0028] 3. The amination mineral powder of the present invention changes the charge characteristics of the cementitious material, reduces the electrostatic repulsion between particles, makes the particles easier to approach and react, and accelerates the hydration rate of the cementitious material; at the same time, the modified mineral powder can provide additional nucleation points, which promotes the faster formation of more hydration products, thereby reducing the final setting time.
[0029] 4. The thiolated fly ash of the present invention has better dispersibility after modification, and can be better filled into the gaps between the particles of the cementitious material, thereby increasing the density of the material, reducing the porosity, and thus improving the compressive strength; at the same time, the thiolated fly ash can absorb moisture to a certain extent, maintain the internal humidity through the material, and prevent volume shrinkage and cracking caused by excessive water loss, thereby maintaining a high compressive strength of the cementitious material.
[0030] 5. The modified gypsum of the present invention is surface treated with γ-glycidyloxypropyltrimethoxysilane to introduce epoxy groups, which can form a network structure inside the material to prevent cracks from rapidly extending from one area to the entire material, thereby improving the flexural properties of the material; the small size of the citric acid carbon quantum dots in the citric acid carbon quantum dots doped red mud enables it to fill the gaps between the red mud particles, thereby increasing the density of the material, reducing the porosity, and further improving the flexural strength of the cementitious material. DETAILED DESCRIPTION
[0031] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0032] The sources of some components in the embodiments and comparative examples are as follows:
[0033] Mineral powder, product number YW0001, purchased from Jiangyin Yongwang Chemical Co., Ltd.;
[0034] Fly ash, product number A01085, was purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0035] Gypsum, brand 20140, purchased from Weifang Shengchuan Chemical Co., Ltd.;
[0036] Red mud, item number h858558, was purchased from Lingshou Yixin Mineral Products Processing Plant;
[0037] Anhydrous ethanol, CAS No. 364-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0038] DL-alanine, CAS No. 302-72-7, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0039] Ammonia water, CAS No. 1336-21-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0040] (3-Mercaptopropyl)triethoxysilane, CAS No. 14814-09-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0041] Glacial acetic acid, CAS No. 64-19-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0042] γ-Glycidyloxypropyltrimethoxysilane, CAS No. 2530-83-8, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0043] Citric acid, CAS No. 77-92-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0044] Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0045] Embodiment 1: This embodiment provides a method for preparing a low-carbon cementitious material for preparing a highway roadbed, comprising the following steps:
[0046] Preparation of mercaptolated fly ash: In parts by weight, 82 parts of anhydrous ethanol, 13 parts of deionized water and 5 parts of ammonia water are mixed, stirred at 32° C. for 14 minutes, and then 17 parts of fly ash and 3 parts of (3-mercaptopropyl)triethoxysilane are added and stirred for 21 hours. After the reaction is completed, solid matter is obtained by centrifugation, and the solid matter is washed with anhydrous ethanol and dried to obtain the mercaptolated fly ash.
[0047] Preparation of modified gypsum: By weight, 32 parts of anhydrous ethanol and 12 parts of deionized water are mixed evenly, the pH is adjusted to 4.3 with glacial acetic acid, and then 3 parts of γ-glycidyloxypropyltrimethoxysilane and 9 parts of gypsum are added and stirred for 45 minutes, filtered, washed, and dried to obtain the modified gypsum.
[0048] Preparation of citric acid carbon quantum dots doped with red mud: (1) 3 parts of citric acid were evenly spread on the bottom of a beaker by weight, and heat-treated in a vacuum drying oven (temperature of 208°C, time of 2h); after the heat treatment, the solid was naturally cooled to room temperature, and then 11 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L was added to the solid, stirred evenly, and dialyzed, freeze-dried, and ground to obtain the citric acid carbon quantum dots;
[0049] (2) In parts by weight, 3 parts of glacial acetic acid were added to 185 parts of deionized water, and then 17 parts of red mud and 7 parts of citric acid carbon quantum dots were added and stirred for 3 hours, frozen at -4°C for 21 hours, and then vacuum freeze-dried (vacuum degree of 9 Pa, temperature of -22°C, time of 54 hours) to obtain the citric acid carbon quantum dot-doped red mud.
[0050] Step S1: 105 parts of mineral powder are weighed by weight and added to 460 parts of anhydrous ethanol, and ultrasonically dispersed for 2 hours to obtain a suspension; 22 parts of DL-alanine are added to the suspension, heated to 76°C and stirred for 1 hour, and filtered, washed and dried to obtain the amination mineral powder;
[0051] Step S2: In parts by weight, 55 parts of amination mineral powder, 25 parts of thiolated fly ash and 15 parts of modified gypsum are added to 110 parts of deionized water for a first stirring treatment (stirring speed of 650 r / min, stirring time of 5 min), and then 5 parts of citric acid carbon quantum dot-doped red mud are added for a second stirring treatment (stirring speed of 330 r / min, stirring time of 12 min) to obtain a low-carbon cementitious material for preparing a highway roadbed.
[0052] Embodiment 2: This embodiment provides a method for preparing a low-carbon cementitious material for preparing a highway roadbed, comprising the following steps:
[0053] Preparation of mercaptolated fly ash: In parts by weight, 84 parts of anhydrous ethanol, 16 parts of deionized water and 5 parts of ammonia water are mixed, stirred at 34° C. for 16 minutes, and then 18 parts of fly ash and 3 parts of (3-mercaptopropyl)triethoxysilane are added and stirred for 22 hours. After the reaction is completed, solid matter is obtained by centrifugation, and the solid matter is washed with anhydrous ethanol and dried to obtain the mercaptolated fly ash.
[0054] Preparation of modified gypsum: By weight, 38 parts of anhydrous ethanol and 13 parts of deionized water are mixed evenly, the pH is adjusted to 4.4 with glacial acetic acid, and then 3 parts of γ-glycidyloxypropyltrimethoxysilane and 9 parts of gypsum are added and stirred for 50 minutes, filtered, washed, and dried to obtain the modified gypsum.
[0055] Preparation of citric acid carbon quantum dots doped with red mud: (1) 3 parts by weight of citric acid were evenly spread on the bottom of a beaker and heat treated in a vacuum drying oven (temperature: 210°C, time: 1 h); after the heat treatment, the solid was naturally cooled to room temperature to obtain a solid, and then 12 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L was added to the solid, stirred evenly, and dialyzed, freeze-dried, and ground to obtain the citric acid carbon quantum dots;
[0056] (2) In parts by weight, 3 parts of glacial acetic acid were added to 190 parts of deionized water, and then 18 parts of red mud and 7 parts of citric acid carbon quantum dots were added and stirred for 3 hours, frozen at -4°C for 22 hours, and then vacuum freeze-dried (vacuum degree of 10 Pa, temperature of -26°C, time of 60 hours) to obtain the citric acid carbon quantum dot-doped red mud.
[0057] Step S1: 110 parts of mineral powder are weighed by weight and added to 480 parts of anhydrous ethanol, and ultrasonically dispersed for 1 hour to obtain a suspension; 23 parts of DL-alanine are added to the suspension, heated to 77°C and stirred for 0.5 hour, and filtered, washed and dried to obtain the amination mineral powder;
[0058] Step S2: In parts by weight, 50 parts of amination mineral powder, 30 parts of thiolated fly ash and 15 parts of modified gypsum are added to 120 parts of deionized water for a first stirring treatment (stirring speed of 700 r / min, stirring time of 6 min), and then 7 parts of citric acid carbon quantum dot-doped red mud are added for a second stirring treatment (stirring speed of 360 r / min, stirring time of 13 min) to obtain a low-carbon cementitious material for preparing a highway roadbed.
[0059] Embodiment 3: This embodiment provides a method for preparing a low-carbon cementitious material for preparing a highway roadbed, comprising the following steps:
[0060] Preparation of mercaptolated fly ash: In parts by weight, 88 parts of anhydrous ethanol, 17 parts of deionized water and 5 parts of ammonia water are mixed, stirred at 38° C. for 19 minutes, and then 19 parts of fly ash and 3 parts of (3-mercaptopropyl)triethoxysilane are added and stirred for 23 hours. After the reaction is completed, solid matter is obtained by centrifugation, and the solid matter is washed with anhydrous ethanol and dried to obtain the mercaptolated fly ash.
[0061] Preparation of modified gypsum: By weight, 42 parts of anhydrous ethanol and 14 parts of deionized water were mixed evenly, the pH was adjusted to 4.7 with glacial acetic acid, and then 3 parts of γ-glycidyloxypropyltrimethoxysilane and 9 parts of gypsum were added and stirred for 55 minutes, filtered, washed and dried to obtain the modified gypsum.
[0062] Preparation of citric acid carbon quantum dots doped with red mud: (1) 3 parts of citric acid were evenly spread on the bottom of a beaker by weight, and heat-treated in a vacuum drying oven (temperature of 215°C, time of 2 hours); after the heat treatment was completed, the solid was naturally cooled to room temperature to obtain a solid, and then 13 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L was added to the solid, stirred evenly, and dialyzed, freeze-dried, and ground to obtain the citric acid carbon quantum dots;
[0063] (2) In parts by weight, 3 parts of glacial acetic acid were added to 195 parts of deionized water, and then 19 parts of red mud and 7 parts of citric acid carbon quantum dots were added and stirred for 3 hours, frozen at -4°C for 23 hours, and then vacuum freeze-dried (vacuum degree of 11 Pa, temperature of -28°C, time of 66 hours) to obtain the citric acid carbon quantum dot-doped red mud.
[0064] Step S1: 115 parts of mineral powder are weighed by weight and added to 490 parts of anhydrous ethanol, and ultrasonically dispersed for 2 hours to obtain a suspension; 24 parts of DL-alanine are added to the suspension, heated to 78°C and stirred for 1 hour, and filtered, washed and dried to obtain the amination mineral powder;
[0065] Step S2: In parts by weight, 60 parts of amination mineral powder, 15 parts of thiolated fly ash and 10 parts of modified gypsum are added to 130 parts of deionized water for a first stirring treatment (stirring speed of 750 r / min, stirring time of 7 min), and then 10 parts of citric acid carbon quantum dot-doped red mud are added for a second stirring treatment (stirring speed of 380 r / min, stirring time of 14 min) to obtain a low-carbon cementitious material for preparing a highway roadbed.
[0066] Embodiment 4: This embodiment provides a method for preparing a low-carbon cementitious material for preparing a highway roadbed, comprising the following steps:
[0067] Preparation of mercaptolated fly ash: In parts by weight, 90 parts of anhydrous ethanol, 20 parts of deionized water and 6 parts of ammonia water are mixed, stirred at 40°C for 10 minutes, and then 20 parts of fly ash and 4 parts of (3-mercaptopropyl)triethoxysilane are added and stirred for 24 hours. After the reaction is completed, solid matter is obtained by centrifugation, and the solid matter is washed with anhydrous ethanol and dried to obtain the mercaptolated fly ash.
[0068] Preparation of modified gypsum: By weight, 45 parts of anhydrous ethanol and 15 parts of deionized water are mixed evenly, the pH is adjusted to 4.2 with glacial acetic acid, and then 4 parts of γ-glycidyloxypropyltrimethoxysilane and 10 parts of gypsum are added and stirred for 60 minutes, filtered, washed and dried to obtain the modified gypsum.
[0069] Preparation of citric acid carbon quantum dots doped with red mud: (1) 4 parts of citric acid were evenly spread on the bottom of a beaker by weight, and heat-treated in a vacuum drying oven (temperature of 220°C, time of 1 h); after the heat treatment, the solid was naturally cooled to room temperature, and then 14 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L was added to the solid, stirred evenly, and dialyzed, freeze-dried, and ground to obtain the citric acid carbon quantum dots;
[0070] (2) In parts by weight, 4 parts of glacial acetic acid were added to 200 parts of deionized water, and then 20 parts of red mud and 8 parts of citric acid carbon quantum dots were added and stirred for 4 hours, frozen at -4°C for 24 hours, and then vacuum freeze-dried (vacuum degree of 12 Pa, temperature of -30°C, time of 48 hours) to obtain the citric acid carbon quantum dot-doped red mud.
[0071] Step S1: 120 parts of mineral powder are weighed by weight and added to 500 parts of anhydrous ethanol, and ultrasonically dispersed for 2 hours to obtain a suspension; 25 parts of DL-alanine are added to the suspension, heated to 80° C. and stirred for 0.5 hours, and the amination mineral powder is obtained after suction filtration, washing and drying;
[0072] Step S2: In parts by weight, 70 parts of amination mineral powder, 30 parts of thiolated fly ash and 20 parts of modified gypsum are added to 140 parts of deionized water for a first stirring treatment (stirring speed is 800 r / min, stirring time is 4 min), and then 15 parts of citric acid carbon quantum dot-doped red mud are added for a second stirring treatment (stirring speed is 400 r / min, stirring time is 10 min) to obtain a low-carbon cementitious material for preparing a highway roadbed.
[0073] Embodiment 5: This embodiment provides a method for preparing a low-carbon cementitious material for preparing a highway roadbed, comprising the following steps:
[0074] Preparation of mercaptolated fly ash: In parts by weight, 80 parts of anhydrous ethanol, 10 parts of deionized water and 4 parts of ammonia water are mixed, stirred at 30° C. for 10 minutes, and then 16 parts of fly ash and 2 parts of (3-mercaptopropyl)triethoxysilane are added and stirred for 20 hours. After the reaction is completed, solid matter is obtained by centrifugation, and the solid matter is washed with anhydrous ethanol and dried to obtain the mercaptolated fly ash.
[0075] Preparation of modified gypsum: By weight, 30 parts of anhydrous ethanol and 10 parts of deionized water are mixed evenly, the pH is adjusted to 4.8 with glacial acetic acid, and then 2 parts of γ-glycidyloxypropyltrimethoxysilane and 8 parts of gypsum are added and stirred for 40 minutes, filtered, washed, and dried to obtain the modified gypsum.
[0076] Preparation of citric acid carbon quantum dots doped with red mud: (1) 2 parts by weight of citric acid were evenly spread on the bottom of a beaker and heat treated in a vacuum drying oven (temperature: 200°C, time: 2 h); after the heat treatment, the solid was naturally cooled to room temperature to obtain a solid, and then 10 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L was added to the solid, stirred evenly, and dialyzed, freeze-dried, and ground to obtain the citric acid carbon quantum dots;
[0077] (2) In parts by weight, 2 parts of glacial acetic acid were added to 180 parts of deionized water, and then 16 parts of red mud and 6 parts of citric acid carbon quantum dots were added and stirred for 2 hours, frozen at -4°C for 20 hours, and then vacuum freeze-dried (vacuum degree of 8 Pa, temperature of -20°C, time of 72 hours) to obtain the citric acid carbon quantum dot-doped red mud.
[0078] Step S1: 100 parts of mineral powder are weighed by weight and added to 450 parts of anhydrous ethanol, and ultrasonically dispersed for 1 hour to obtain a suspension; 20 parts of DL-alanine are added to the suspension, heated to 75° C. and stirred for 1 hour, and the amination mineral powder is obtained after suction filtration, washing and drying;
[0079] Step S2: In parts by weight, 40 parts of amination mineral powder, 10 parts of thiolated fly ash and 5 parts of modified gypsum are added to 100 parts of deionized water for a first stirring treatment (stirring speed is 600r / min, stirring time is 8min), and then 2 parts of citric acid carbon quantum dot-doped red mud are added for a second stirring treatment (stirring speed is 300r / min, stirring time is 15min) to obtain a low-carbon cementitious material for preparing a highway roadbed.
[0080] Comparative Example 1: This comparative example provides a method for preparing a cementitious material. The difference from Example 1 is that commercially available mineral powder is used instead of amination mineral powder, commercially available fly ash is used instead of thiol fly ash, commercially available gypsum is used instead of modified gypsum, and commercially available red mud is used instead of citric acid carbon quantum dot-doped red mud.
[0081] Comparative Example 2: This comparative example provides a method for preparing a cementitious material. The difference from Comparative Example 1 is that amination mineral powder is used instead of commercially available mineral powder.
[0082] Comparative Example 3: This comparative example provides a method for preparing a cementitious material. The difference from Comparative Example 1 is that mercaptolated fly ash is used instead of commercially available fly ash.
[0083] Comparative Example 4: This comparative example provides a method for preparing a cementitious material. The difference from Comparative Example 1 is that modified gypsum is used instead of commercially available gypsum.
[0084] Comparative Example 5: This comparative example provides a method for preparing a cementitious material. The difference from Comparative Example 1 is that citric acid carbon quantum dots-doped red mud is used instead of commercially available red mud.
[0085] Comparative Example 6: This comparative example provides a method for preparing a cementitious material. The difference from Example 1 is that commercially available mineral powder is used instead of amination mineral powder.
[0086] Comparative Example 7: This comparative example provides a method for preparing a cementitious material. The difference from Example 1 is that commercially available fly ash is used instead of mercaptolated fly ash.
[0087] Comparative Example 8: This comparative example provides a method for preparing a cementitious material. The difference from Example 1 is that commercially available gypsum is used instead of modified gypsum.
[0088] Comparative Example 9: This comparative example provides a method for preparing a cementitious material. The difference from Example 1 is that commercially available red mud is used instead of citric acid carbon quantum dots-doped red mud.
[0089] The performance of the gelling materials provided in the above embodiments and comparative examples was tested, and the specific testing method is as follows:
[0090] (1) Setting time test
[0091] The test is carried out with reference to the requirements of GB / T 1346-2011 Test methods for water consumption, setting time and stability of cement of standard consistency.
[0092] (2) Flexural strength test
[0093] The test shall be carried out with reference to the requirements of "GB / T 17671-2021 Test method for strength of cement mortar (ISO method)".
[0094] (3) Compressive strength test
[0095] Refer to the requirements of "GB / T 17671-2021 Test method for strength of cement mortar (ISO method)" for testing.
[0096] The above performance test data is shown in Table 1.
[0097] Table 1 Performance test results
[0098] Final setting time (min) Flexural strength (MPa) Compressive strength (MPa) Example 1 691 9.38 59.35 Example 2 687 9.86 62.41 Example 3 682 10.81 60.99 Example 4 678 10.93 63.15 Example 5 695 9.15 59.18 Comparative Example 1 768 5.42 50.26 Comparative Example 2 743 5.48 50.38 Comparative Example 3 764 6.29 50.42 Comparative Example 4 761 5.51 53.64 Comparative Example 5 759 5.58 53.79 Comparative Example 6 723 7.85 56.14 Comparative Example 7 727 7.96 56.32 Comparative Example 8 725 7.89 56.25 Comparative Example 9 729 8.03 56.43
[0099] From the above content, it can be seen that the present invention prepares low-carbon cementitious materials for highway roadbeds (Examples 1 to 3) by aminating the main component of the cementitious material, the mineral powder, thiolating the fly ash, and introducing modified gypsum and citric acid carbon quantum dots to dope red mud. The final setting time of the cementitious material is 678 to 695 min, the flexural strength is 9.15 to 10.93 MPa, and the compressive strength is 59.18 to 63.15 MPa.
[0100] Compared with Example 1, commercially available mineral powder is used to replace amination mineral powder, commercial fly ash is used to replace mercaptolated fly ash, commercial gypsum is used to replace modified gypsum, and commercial red mud is used to replace citric acid carbon quantum dot-doped red mud, the final setting time is increased, and the flexural strength and compressive strength are reduced (Comparative Example 1); compared with Comparative Example 1, amination mineral powder is used to replace commercial mineral powder, and the final setting time is shortened (Comparative Example 2); compared with Comparative Example 1, mercaptolated fly ash is used to replace commercial fly ash, and the flexural strength is improved (Comparative Example 3); compared with Comparative Example 1, modified gypsum is used to replace commercial gypsum, and the compressive strength is improved (Comparative Example 4); compared with Comparative Example 1, citric acid carbon quantum dots are used to dope red mud. Replacing commercially available red mud, the compressive strength is improved (Comparative Example 5); compared with Example 1, using commercially available mineral powder to replace the amination mineral powder, the final setting time is increased, the compressive strength is reduced, and the flexural strength is reduced (Comparative Example 6); compared with Example 1, using commercially available fly ash to replace the thiolated fly ash, the final setting time is increased, the compressive strength is reduced, and the flexural strength is reduced (Comparative Example 7); compared with Example 1, using commercially available gypsum to replace modified gypsum, the final setting time is increased, the compressive strength is reduced, and the flexural strength is reduced (Comparative Example 8); compared with Example 1, using commercially available red mud to replace citric acid carbon quantum dot-doped red mud, the final setting time is increased, the compressive strength is reduced, and the flexural strength is reduced (Comparative Example 9).
[0101] In summary, the present invention prepares a low-carbon cementitious material for the highway roadbed by subjecting the main component of the cementitious material, the mineral powder, to an amination treatment, subjecting the fly ash to a thiol treatment, and introducing modified gypsum and citric acid carbon quantum dots to dope red mud, thereby ensuring that the cementitious material has a suitable final setting time and effectively improving the compressive strength and flexural strength.
[0102] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a low-carbon cementitious material for preparing a highway roadbed, characterized in that: The following steps are involved: Step S1: weigh 100-120 parts of mineral powder by weight, add it to 450-500 parts of anhydrous ethanol, and disperse it by ultrasonic for 1-2 hours to obtain a suspension; Add 20-25 parts of DL-alanine to the suspension, heat it to 75-80°C and stir it for 0.5-1h, filter it, wash it and dry it to obtain the aminated mineral powder; Step S2: by weight, 40 to 70 parts of amination ore powder, 10 to 30 parts of fly ash and 5 to 20 parts of gypsum are added to 100 to 140 parts of deionized water for a first stirring treatment, and then 2 to 15 parts of red mud are added for a second stirring treatment to obtain a low-carbon cementitious material for preparing a highway roadbed; The fly ash is mercaptolated fly ash; The preparation method of the mercaptolated fly ash comprises: mixing 80-90 parts of anhydrous ethanol, 10-20 parts of deionized water and 4-6 parts of ammonia water by weight, stirring for 10-20 minutes at 30-40° C., then adding 16-20 parts of fly ash and 2-4 parts of (3-mercaptopropyl) triethoxysilane, stirring for reaction for 20-24 hours, centrifuging to obtain a solid after the reaction is completed, washing the solid with anhydrous ethanol, and drying to obtain the mercaptolated fly ash; The gypsum is modified gypsum; The preparation method of the modified gypsum comprises: mixing 30-45 parts of anhydrous ethanol and 10-15 parts of deionized water uniformly by weight, adjusting the pH value to 4.2-4.8 with glacial acetic acid, then adding 2-4 parts of γ-glycidyloxypropyltrimethoxysilane and 8-10 parts of gypsum, stirring for 40-60 minutes, filtering, washing and drying to obtain the modified gypsum.
2. The method for preparing a low-carbon cementitious material for preparing a highway roadbed according to claim 1, characterized in that: The red mud is citric acid carbon quantum dots doped red mud; The preparation method of the citric acid carbon quantum dots doped red mud comprises: adding 2 to 4 parts of glacial acetic acid to 180 to 200 parts of deionized water, adding 16 to 20 parts of red mud and 6 to 8 parts of citric acid carbon quantum dots, stirring for 2 to 4 hours, freezing at -4°C for 20 to 24 hours, and then performing vacuum freeze drying to obtain the citric acid carbon quantum dots doped red mud.
3. The method for preparing a low-carbon cementitious material for preparing a highway roadbed according to claim 2, characterized in that: The vacuum freeze-drying conditions include: vacuum degree of 8-12 Pa, temperature of -20--30° C., and time of 48-72 h.
4. The method for preparing a low-carbon cementitious material for preparing a highway roadbed according to claim 2, characterized in that: The preparation method of the citric acid carbon quantum dots comprises: by weight, 2 to 4 parts of citric acid are evenly spread on the bottom of a beaker, and heat-treated in a vacuum drying oven; after the heat treatment is completed, the solid is naturally cooled to room temperature to obtain a solid, and then 10 to 14 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L is added to the solid, stirred evenly, and dialyzed, freeze-dried, and ground to obtain the citric acid carbon quantum dots.
5. The method for preparing a low-carbon cementitious material for preparing a highway roadbed according to claim 4, characterized in that: The heat treatment temperature is 200-220° C. and the time is 1-2 hours.
6. The method for preparing a low-carbon cementitious material for preparing a highway roadbed according to claim 1, characterized in that: The stirring speed of the first stirring treatment is 600-800 r / min, and the stirring time is 4-8 min.
7. The method for preparing a low-carbon cementitious material for preparing a highway roadbed according to claim 1, characterized in that: The stirring speed of the second stirring treatment is 300-400 r / min, and the stirring time is 10-15 min.
8. A low-carbon cementitious material for preparing a highway roadbed, characterized in that: Prepared according to the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Low-carbon impervious early-strength water-reducing cementing material and preparation method thereof
CN117024014A
Method for preparing thiol functional fly ash and application thereof
CN109569499A
Modified fly ash material grafted with amino acid through irradiation, preparation and application thereof
CN113842872A
Cited By
Green low-carbon cementing material for roadbed and preparation method of green low-carbon cementing material
CN120590136A
Green low-carbon cementitious material for roadbed and preparation method thereof
CN120590136B